Atmospheric horizontal gradients measured with eight co-located GNSS stations and a microwave radiometer - T. Ning; G. Elgered (Atmospheric Measurement Techniques)
We used eight co-located global navigation satellite system (GNSS) stations with different antenna mounts to estimate atmospheric signal propagation delays in the zenith direction and linear horizontal gradients. The gradients are compared with the results from a water vapour radiometer (WVR). The water drops in the atmosphere have a negative influence on the retrieval accuracy of the WVR. Hence, we see better agreement using WVR data with a liquid water content (LWC) less than 0.05 mm compared to when LWC values of up to 0.7 mm are included. We used two different constraints when estimating the linear gradients from the GNSS data. Using a weak constraint enhances the GNSS estimates to track large gradients of short duration at the cost of increased formal errors. To mitigate random noise in the GNSS gradients, we adopted a fusion approach, averaging estimates from the GNSS stations. This resulted in significant improvements for the agreement with the WVR data, a maximum of 17 % increase in the correlation, and a 14 % reduction in the root mean square (RMS) difference for the east gradients. The corresponding values for the north gradients are both 25 %. Overall, no large differences in terms of quality are observed for the eight GNSS stations. However, one station shows slightly poorer agreement for the north gradients compared to the others. This is attributed to the station's proximity to a radio telescope, which causes data loss of observations at low-elevation angles in the south-south-west direction.